Порівняльний аналіз Django, Flask та Fastapi - Солохін, А. Є. (ХНУРЕ, 2024)
This comprehensive comparative analysis delves into the intricate features and functionalities of Django, Flask, and FastAPI. By meticulously scrutinizing their attributes, this analysis aims to offer a nuanced understanding of their capabilities, strengths, and limitations across various parameters. The evaluation encompasses crucial aspects such as scalability, ease of use, and performance, providing invaluable insights to developers navigating the labyrinth of framework selection. With a keen focus on deciphering how these frameworks measure up against each other, this analysis serves as a guiding beacon, empowering developers to make well-informed decisions tailored to the unique requisites of their projects.
Keywords: Django; Flask; Fastapi